(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The lexical aspect of learning a foreign language is one of the most difficult aspects of foreign language teaching practice in a technical university. A small vocabulary makes students feel insecure and even often reluctant to speak a foreign language, so expanding students’ vocabulary is one of the main tasks in a foreign language class. It is known that qualitatively formed lexical skills are the main condition for successful communication in a foreign language, and violations of lexical and semantic norms lead to various semantic errors that make speech communicatively imperfect or incomprehensible.